2014
DOI: 10.1021/ic5003429
|View full text |Cite
|
Sign up to set email alerts
|

σ-Bond Activation of Small Molecules and Reactions Catalyzed by Transition-Metal Complexes: Theoretical Understanding of Electronic Processes

Abstract: σ-Bond activations of R1-R2 and R1-X1 (R1, R2 = H, alkyl, aromatics, etc.; X1 = electronegative group) by transition-metal complexes are classified into two main categories: σ-bond activation by a metal (M) center and that by a metal-ligand bond. The former is classified into two subcategories: concerted oxidative addition to M and stepwise oxidative addition via nucleophilic attack of M. The latter is also classified into two subcategories: heterolytic activaton by M-X2 (X2 = anion ligand) and oxidative addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 107 publications
4
43
0
Order By: Relevance
“…Because of this characteristicf eature, this type of s-bond metathesis reaction is named "heterolytic sbond activation". [15] In the SiÀFb ond activation by the iridium hydride complex B1,t he iridium center forms an ew bond with the electropositives ilicon atom and the hydridel igand forms an ew bond with the electronegative Fa tom, as shown in Figure 3. This situation is opposite to that of normal"hetero- www.chemeurj.org lytic s-bond activation".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this characteristicf eature, this type of s-bond metathesis reaction is named "heterolytic sbond activation". [15] In the SiÀFb ond activation by the iridium hydride complex B1,t he iridium center forms an ew bond with the electropositives ilicon atom and the hydridel igand forms an ew bond with the electronegative Fa tom, as shown in Figure 3. This situation is opposite to that of normal"hetero- www.chemeurj.org lytic s-bond activation".…”
Section: Resultsmentioning
confidence: 99%
“…Three mechanistic scenarios are conceivable to account for the SiÀF s-bond activation by iridium hydride 2 ( Figure 2): www.chemeurj.org a) concerted oxidative addition, b) S N 2t ype reaction, and c) sbond metathesis. [15] To determine the pathway through which the reaction occurs, density functionalt heory (DFT) calculations were performed at the B3PW91 [16] level of theory using model compounds in which the phenyl groups at phosphorus were replaced by methyl groups. [18] Consideringt hese results, the initial step in the reactioni sp robably the formation of A1 or B1, upon displacemento ft wo PPh 3 at Ir by the phosphine sidearms of 1a (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The authors confirmed the electrophilic nature of the active oxidizing species. The latter demonstrated high 3˝/2˝ratios (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), alcohol/ketone ratios > 5, and high stereospecificity in the oxidation of cis-1,2-dimethylcyclohexane [187]; kinetic studies revealed a sizable kinetic isotopic effect (k H /k D 4.5-4.7), indicating that that the H atom lies on the reaction coordinate and participates in the C-H bond breaking step. Altogether, the experimental data provided indirect evidence in favor of the participation of a high-valent (presumably oxometal(V) [188]) species, ruling out the contribution of a free-radical-driven oxidation pathway.…”
Section: New Types Of Ligands and Catalystsmentioning
confidence: 99%
“…Transition metal complexes can serve a myriad of functions. These include, but are not limited to, chemotherapeutic agents [1][2][3], CO 2 activation [4][5][6][7], artificial water splitting [8][9][10][11][12], C-H and C-C activation [13][14][15][16][17], and catalysis of numerous other organic transformations [18][19][20][21]. This diversity in function is the result of stark differences in the electronic structure of transition metal complexes in contrast to the chemistry exhibited by main group elements.…”
Section: Introductionmentioning
confidence: 99%